Procedural safety, short and long-term follow up after pacemaker implantation in nonagenarians. (19th May 2022) - Meynet, I; Tricomi, L; Ferraro, A; Maggio, R; Mazza, A; Ceci, R; Minniti, D; Varbella, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Permanent cardiac stimulation is increasingly necessary in very old patients, due to the augmented life expectancy. This raise concerns in physicians, patients and caregivers, because pacemaker (PM) implantation can be perceived as too invasive for frail patients with significant comorbidities. Purpose: The aim of the present study is to provide data about peri-operative complications, short and long-term survival and their predictors in this specific setting. Materials and methods: All consecutive patients aged ≥90 years undergoing pacemaker implantation in our Centre from 2008 to 2020 were enrolled in the registry. Their baseline and follow up data were recorded in a specific database. Results: Among the 2437 patients undergoing PM implantation in a 13-year period, 153 were nonagenarians (6.3%). Mean age was 92.7±2.3 years. Most of the patients (66.7%) received a ventricular single chamber PM. High-degree atrio-ventricular block was the first indication for implant (59.5%), followed by sick sinus syndrome or atrial fibrillation with slow ventricular response (30.1%). 15.7% patients needed temporary pacing at presentation. 4 patients (2.6%) experienced acute complications: 3 pneumothorax, 1 ventricular lead displacement with need of repositioning. Mean follow up duration was 2.5±2.0 years. 117 patients (78.5%) died during the follow up. Death occurred after a mean of 2.47 years after PM implantation (range 1-3272 days). Survival rates were 70.0%, 35.3% and 10.0% at 1, 3 and 5 years respectively. No pacemaker-related long-term complication was recorded during the follow up. 2 patients underwent generator replacement due to battery end of life. Chronic kidney insufficiency (p = 0.030) and congestive heart failure (p = 0.021) but not age were predictors of precocious mortality (within 1 month). Age at implant and longer length of hospital stay before PM implantation were predictors of long-term death (p = 0.001 and p = 0.043 respectively). Conclusions: Extremely old age should not discourage PM implantation, when indicated; age is obviously predictor of long-term death but is not predictor of precocious mortality. Acute periprocedural complication rate is low and generally comparable to that of younger populations.